Return of genetic and genomic research findings: experience of a pediatric biorepository - Tanya Papaz; Eriskay Liston; Laura Zahavich; Dimitri J. Stavropoulos; Rebekah K. Jobling; Raymond H. Kim; Miriam Reuter; Anastasia Miron; Erwin Oechslin; Tapas Mondal; Lynn Bergin; John F. Smythe; et al. (BMC, 2019)
Abstract Background Assess process, uptake, validity and resource needs for return of actionable research findings to biobank participants. Methods Participants were prospectively enrolled in a multicenter biorepository of childhood onset heart disease. Clinically actionable research findings were reviewed by a Return of Research Results Committee (RRR) and returned to the physician or disclosed directly to the participant through a research genetic counselor. Action taken following receipt of this information was reviewed. Results Genetic data was generated in 1963 of 7408 participants. Fifty-nine new findings were presented to the RRR committee; 20 (34%) were deemed reportable. Twelve were returned to the physician, of which 7 were disclosed to participants (median time to disclosure, 192 days). Seven findings were returned to the research genetic counselor; all have been disclosed (median time to disclosure, 19 days). Twelve families (86%) opted for referral to clinical genetics after disclosure of findings; 7 results have been validated, 5 results are pending. Average cost of return and disclosure per reportable finding incurred by the research program was $750 when utilizing a research genetic counselor; clinical costs associated with return were not included. Conclusions Return of actionable research findings was faster if disclosed directly to the participant by a research genetic counselor. There was a high acceptability amongst participants for receiving the findings, for referral to clinical genetics, and for clinical validation of research findings, with all referred cases being clinically confirmed.